Nieruchomości komunalne jako element zagospodarowania Szadku - Banasiak, Joanna (Biuletyn Szadkowski, 2009)
Under the Act on local government of 8 March 1990 communes gained legal personality and financial autonomy. To be able to provide for the needs of local communities, communes obtained considerable property, mainly real estate. Municipal real property, which consists of land and buildings, is an important factor in the development of communes. In Szadek, communal land constitutes 5.7% of the town’s area, and municipal flats make up 8.75% of all flats. Municipal estate should be used primarily for public purposes and for providing for local housing need. Other uses include undertakings serving commune development and organized investment activity. In addition, municipal real property trading is an important source of local government income.